PENERAPAN TEKNOLOGI BUDIDAYA TANAMAN RAMAH LINGKUNGAN UNTUK PRODUKSI SAYURAN SEHAT DI KELOMPOK WANITA TANI WIJAYA KUSUMA KELURAHAN KAMBU KOTA KENDARI - Andi Khaeruni; Terry Pakki; Asniah Asniah; Nur Isnaini Ulfa; Mirza Asriyanti Arsyad; Agustono Agustono (Jurnal Hilirisasi IPTEKS, 2022)
During the current Covid-19 pandemic, the need for healthy food, including vegetables, is significant to increase the body's immunity to free from infection with the disease. The availability of healthy vegetables can be obtained through using the yard by growing vegetables organically. This activity aims to increase community participation in developing organic agriculture and supporting sustainable agriculture during the Covid-19 pandemic. The target of this program is the community of Kambu Village and the city government of Kambu Village, Kambu District, Kendari City. The activities carried out involve participating in various parties (city governments, communities, students, and academics) through counseling, training, demonstrations, and making demonstration plots for organic vegetable cultivation. This guidance hopes that sustainable organic farming will be realized through this guidance. The results of this activity indicate that community participation, especially among members of the women's farmer group Wijaya Kusuma, Kambu Village, has increased in the use of limited land to cultivate healthy vegetables. Public awareness and knowledge about the importance of applying organic fertilizers and vegetable pesticides (eco-enzymes) are increased through these activities. Increased organic fertilizers and eco-enzymes for household-scale vegetable cultivation by the Wijaya Kusuma Farmer Women's Group, Kambu Village, Kambu Village, Kambu District, Kendari City. Availability of healthy food ingredients in the form of sustainable organic vegetables. The collaboration between the city government and academia is increasingly closely intertwined through the activities carried out.